Effect of Metal Foam Structure on Pool Boiling Heat Transfer Characteristics - Hu Chenyu; Lai Zhancheng; Hu Haitao; Han Weizhe (Zhileng xuebao)
Pool boiling heat transfer characteristics of a refrigerant on heating surfaces of metal foams of different structures were experimentally studied. The test samples were copper foams of different pore densities (5–40 PPI), porosities (0.90 and0.95), and thicknesses (4–8 mm). The experimental results show that the maximum surface heat transfer coefficient of the metal foam increases by 26.4% as pore density increases from 5 to 40 PPI. The foam metal pool boiling heat transfer first increases and then decrease with an increase in thickness and the maximum surface heat transfer coefficient of the metal foam with a porosity of 0.90 is 13.2% larger than that with a porosity of 0.95. According to the experimental results, the boiling heat transfer correlation of the refrigerant on the surface with different structured metal foam is developed. The deviation between the prediction value of the correlation and 95% of the experimental data is within ±30% and the average deviation is 12.2%.